The supply of inorganic fertilizers to smallholder farmers in Mozambique: Evidence for fertilizer policy development - Benson, Todd; Cunguara, Benedito; Mogues, Tewodaj (International Food Policy Research Institute, 2012)
This paper presents the results of a broad study of fertilizer supply to smallholder farmers in Mozambique that was done to assess whether the taxes (explicit or implicit) that are applied at various points along the fertilizer importation and marketing chain, or the absence of key public goods and services, reduces the access that smallholder farmers have to fertilizer. The study involved a review of the literature of fertilizer supply, demand, and use; interviews with key participants in fertilizer importation and marketing in Mozambique; and two surveys—one with farmers and the other with input suppliers—in two farming areas where more fertilizer is used than is the norm for the country as a whole.